Enhancing student well-being and success through AI-driven mental-health support: A case study of AI mental-health chatbot implementation at a South African university (Journal of Student Affairs in Africa, 2025)
Mental health is a critical determinant of student success in higher education. University students continue to face significant psychological challenges, including anxiety, stress, and trauma, issues further intensified by the Covid-19 pandemic. These realities underscore the need for accessible, scalable, and technology-driven mental-health interventions. This study investigates the implementation of Wysa, an AI-powered mental-health chatbot, at a South African higher education institution (HEI). Through a mixed-methods design, the research draws on secondary dashboard analytics and primary user survey data to evaluate adoption rates, engagement patterns, and the nature of interventions accessed. Results reveal that AI-driven mental-health tools can offer cost-effective, confidential, and scalable support to students, with evidence of meaningful usage across diverse student groups. However, amongst some student cohorts, adoption is uneven, influenced by the students’ academic disciplines, help-seeking behaviours, and concerns related to data privacy and trust. The study concluded with practical recommendations for integrating AI chatbots into institutional support services, advocating for a blended care model and student-centred digital mental-health strategies suited to the African higher education context.
Keywords: Student well-being; mental health; AI chatbots; African higher education; preventive interventions; student success